Design and Development of Visual Novel-Based Educational Game to Enhance Computer Basics Understanding for High School Students - Prayoga, Andri; Muhammad, Taofik; Taufiq, Muhammad (Design Journal, 2026)
This study was intended to design and determine the effectiveness of a visual novel-based educational game in enhancing the understanding of basic computer subjects for high school students. The research used the ADDIE model as its development framework, which stands for Analysis, Design, Development, Implementation, and Evaluation. The analysis phase revealed that students were having difficulty understanding concepts about computers because conventional lecture-based teaching methods were being used. The visual novel game was designed by combining narrative storylines with illustrations, interactive quizzes, and decision-making elements to engage students in learning activities. Media and material experts validated the product with feasibility scores of 90% and 88%, both categorized as highly feasible. Implementation involved 26 tenth-grade students who completed pretest and posttest assessments; results indicated significant learning improvement with average scores increasing from 5.81 (41.5%) to 10.77 (76.9%), producing an N-Gain value of 0.61 (medium category). Student response questionnaires indicated high acceptance with an overall score of 87.58%—particularly in game usefulness at 94.23% and learning experience at 91.35%. This proves that visual novel-based educational games can improve student understanding, motivation, and engagement in learning basic computers as an alternative to conventional teaching methods in ICT education.